Jacob solves the system of equations by forming a matrix equation.

4x+y=2
−2x+3y=−22

He multiplies the left side of the coefficient matrix by the inverse matrix.

How does he proceed to the solution?

Drag the choices to correctly complete Jacob's process.

Jacob solves the system of equations by forming a matrix equation 4xy2 2x3y22 He multiplies the left side of the coefficient matrix by the inverse matrix How do class=

Respuesta :

Simultaneous equations can be solved using inverse matrix operation.

The complete steps of Jacob's solution are:

[tex]\left[\begin{array}{cc}4&1\\-2&3\end{array}\right]^{-1} \cdot \left[\begin{array}{cc}4&1\\-2&3\end{array}\right]\left[\begin{array}{c}x&y\end{array}\right] = \frac{1}{14}\left[\begin{array}{cc}3&-1\\2&4\end{array}\right] \cdot \left[\begin{array}{c}2&-22\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \left[\begin{array}{cc}4&1\\-2&3\end{array}\right] \cdot \left[\begin{array}{c}2&-22\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \frac{1}{14} \left[\begin{array}{c}28&-84\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \left[\begin{array}{c}2&-6\end{array}\right][/tex]

We have:

[tex]4x + y = 2[/tex]

[tex]-2x + 4y = -22[/tex]

Calculate the determinant of [tex]\left[\begin{array}{cc}4&1\\-2&3\end{array}\right][/tex]

[tex]|A| = 4 \times 3 -1 \times -2[/tex]

[tex]|A| = 12 +2[/tex]

[tex]|A| = 14[/tex]

So, the inverse matrix becomes

[tex]A = \frac{1}{14}\left[\begin{array}{cc}4&1\\-2&3\end{array}\right][/tex]

Replace the first column with [tex]\left[\begin{array}{c}2&-22\end{array}\right][/tex] to calculate the value of x

[tex]x = \frac{1}{14}\left[\begin{array}{cc}2&1\\-22&3\end{array}\right][/tex]

So, we have:

[tex]x = \frac{1}{14}(2 \times 3 - 1 \times -22)[/tex]

[tex]x = \frac{1}{14}(6 +22)[/tex]

[tex]x = \frac{1}{14}(28)[/tex]

[tex]x = 2[/tex]

Replace the second column with [tex]\left[\begin{array}{c}2&-22\end{array}\right][/tex] to calculate the value of y

[tex]y = \frac{1}{14}\left[\begin{array}{cc}4&2\\-2&-22\end{array}\right][/tex]

So, we have:

[tex]y = \frac{1}{14}(4 \times -22 - 2 \times -2)[/tex]

[tex]y = \frac{1}{14}(-88 +4)[/tex]

[tex]y = \frac{1}{14}(-84)[/tex]

[tex]y = -6[/tex]

Hence, the complete process is:

[tex]\left[\begin{array}{cc}4&1\\-2&3\end{array}\right]^{-1} \cdot \left[\begin{array}{cc}4&1\\-2&3\end{array}\right]\left[\begin{array}{c}x&y\end{array}\right] = \frac{1}{14}\left[\begin{array}{cc}3&-1\\2&4\end{array}\right] \cdot \left[\begin{array}{c}2&-22\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \left[\begin{array}{cc}4&1\\-2&3\end{array}\right] \cdot \left[\begin{array}{c}2&-22\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \frac{1}{14} \left[\begin{array}{c}28&-84\end{array}\right][/tex]

[tex]\left[\begin{array}{c}x&y\end{array}\right] = \left[\begin{array}{c}2&-6\end{array}\right][/tex]

Read more about matrices at:

https://brainly.com/question/11367104